MPB, a novel berberine derivative, enhances lysosomal and bactericidal properties via TGF‐β–activated kinase 1‐dependent activation of the transcription factor EB. Issue 1 (30th August 2018) - Liu, Xiaojia; Zhang, Na; Liu, Yang; Liu, Lu; Zeng, Qingxuan; Yin, Mingxiao; Wang, Yanxiang; Song, Danqing; Deng, Hongbin
ABSTRACT: Lysosome has a crucial role in clearance of endocytosed pathogens from the cell. Small molecules that can boost lysosome function and bactericidal ability to cope with subsequent infection are urgently needed. Here, we report that MPB, a novel berberine derivative, induced lysosome‐based degradation and clearance of methicillin‐resistant Staphylococcus aureus and enteroinvasive Escherichia coli in macrophages. MPB caused nuclear translocation of transcription factor EB (TFEB), which boosted expression of lysosome genes. TFEB silencing repressed the MPB‐mediated enhancements in degradation and bacterial eradication. MPB switched on TFEB nuclear translocation by coupling 2 parallel signaling pathways. MPB‐triggered JNK activation led to 14‐3‐3δ being released from TFEB, which, in turn, caused TFEB nuclear translocation. In addition, MPB induced AMPK activation and subsequent inhibition of mechanistic target of rapamycin activity, which also contributed to TFEB nuclear translocation. Importantly, genetical or pharmaceutical inhibition of TGF‐β–activated kinase 1 (TAK1) reduced MPB action remarkably. MPB acted through TAK1 at lysine 158 to activate JNK and AMPK and, thus, induced TFEB‐dependent bactericidal activity in macrophages. Therefore, our study reveals a novel mechanism by which MPB controls JNK and AMPK phosphorylation cascades to activate lysosomal function and bactericidal activity via TAK1 K158–dependent manner, which may offer insight into novel therapeutic strategies to control bacterial infection.—Liu, X., Zhang, N., Liu, Y., Liu, L., Zeng, Q., Yin, M., Wang, Y., Song, D., Deng, H. MPB, a novel berberine derivative, enhances lysosomal and bactericidal properties via TGF‐β–activated kinase 1‐dependent activation of the transcription factor EB. FASEB J. 33, 1468–1481 (2019). www.fasebj.org